Two point diagonally block method for solving boundary value problems with Robin boundary conditions - Nadirah, Mohd Nasir; Zanariah, Abdul Majid; Fudziah, Ismail; Norfifah, Bachok (Universiti Putra Malaysia, 2019)
This numerical study emphasizes on fifth order multistep block method for solving second order boundary value problems(BVPs) imposing Robin boundary conditions. The shooting technique will be utilized to compute the approximate solutions at two point simultaneously. The implementation of predictor-corrector scheme follows the PE(CE)r mode. Numerical results are presented to give a clear view of the performances for the proposed method. The order and stability of the method are also discussed.